Perancangan SIMRS Terintegrasi Modul Human Resource Development Pada Rumah Sakit Pendidikan - Primaningrat Gita Puspita, A.A; Sukarsa, I Made; Oka Sudana, A.A. K. (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2015)
Human resources at the hospital consists of many kind of disciplines and professions that can be divided into Medical and Non-Medical Personnel. Management Information System Human Resource Development Module needed to accelerate and facilitate the processing of employee data and helpful for management decision making. The module also needs to be integrated with the Payroll Module to facilitate the process of Payroll and remuneration in the hospital. Stage of the system design was conducted by TAS (Total Architecture Syntesis), they are the determination of initial scope, determination of needs, determination of business processes, system design, and evaluation. Human Resource Development Module contains the data collection process, transfer, performance assessment, absences, schedulin, hiring, and reporting. Payroll module contains Payroll and remuneration. This work described by Data Flow Diagrams, Database Structure, and User Interface Design. This design can be used as guidelines for programmers in the manufacture of Hospital Information System are integrated.
Keywords: Sistem Informasi Rumah Sakit; Total Architecture Syntesis; Kepegawaian; Penggajian